The anthropology of the heart as a way to ecumenical dialogue - Kraśniewska, Jolanta (Kwartalnik Naukowy Fides et Ratio, 2021)
Abstract: The article describes, taking as its main starting point the encyclical Fides et ratio, the importance of the way of thinking appropriate to the culture of the Christian East in the relationship between reason and faith. The encyclical of John Paul II has many different aspects, including the not often emphasised ecumenical and dialogical aspects. The Pope, who held Eastern (Orthodox) Christianity in high esteem and appreciated the Slavic cultural code, also positively points to this method of discovering the truth. In this context, the anthropology of the heart is particularly important (metaphysics of the heart, mysticism of the heart or spirituality of the heart), which enriches and complements the Western way of thinking and of discovering anthropological and theological truth. The anthropology of the heart also appears in the West and for this reason it has an ecumenical significance which is important for the dialogue between Catholicism and Orthodoxy.